Rocky Balboa (2006) [videorecording (DVD)] - Stallone, Sylvester; Young, Burt; Ventimiglia, Milo, 1977- (Sony Pictures Home Entertainment, 2007)
Rocky is a former heavyweight boxing champion who is known and renown throughout the world for going the distance, finds a new venture: giving back to his community. He finds himself, once more, at opposing side of opportunity, not unlike the one he has seen decades ago. Heavyweight champ Mason Dixon and his representation offer Rocky a shot for the title. For Balboa, it'll be one last hurrah he'll never forget. A look at going full circle and wanting more, when life turns out how you least expect it and then some.